A cross-sectional study to assess the prevalence of DSM-5 specific learning disorders in representative school samples from the second to sixth grade in Brazil. - Fortes, Isabela; Paula, Cristiane; Oliveira, Melaine; Bordin, Isabel; de Jesus Mari, Jair; Rohde, Luis (European Child & Adolescent Psychiatry, 2016)
Little is known about specific learning disorder (SLD) in low- and middle-income countries (LMICs), and even less from representative school samples in small size cities outside huge urban centers. Few studies addressed the new DSM-5 criteria for SLDs. We investigated the prevalence of DSM-5 SLDs, their comorbidities and correlates in school samples of students from the second to sixth grades living in median cities from four different geographic regions in Brazil. A national test for academic performance covering reading, writing and mathematical abilities was applied. Psychiatric diagnoses were assessed by the K-SADS-PL applied to the primary caregiver. A total of 1618 children and adolescents were included in the study. The following prevalence rates of SLDs were found: 7.6 % for global impairment, 5.4 % for writing, 6.0 % for arithmetic, and 7.5 % for reading impairment. Attention-deficit/hyperactivity disorder (ADHD) was the only comorbidity significantly associated with SLD with global impairment ( p = 0.031). Anxiety disorders and ADHD were associated with SLD with arithmetic impairment. Significant differences were detected in prevalence rates among cities, and several socio-demographic correlates (age, gender, IQ, and socioeconomic status) were significantly associated with SLD with global impairment in our sample. Careful validation and normatization of instruments to assess academic performance is a major problem in LMICs. As expected, we found a significant heterogeneity in prevalence rates of SLD according to geographic regions considering that Brazil is a country with a robust diversity. SLD with global and arithmetic impairment was significantly associated with psychiatric comorbidities.